Hour of the Olympics - Osborne, Mary Pope.; Murdocca, Sal. (New York : Random House, 1998)
Their magic tree house takes Jack and Annie back to retrieve a lost story in ancient Greece, where they witness the original Olympic games and are surprised to find what girls of the time were not allowed to do.
"A Stepping Stone book."
"RL:2.3"--Page 4 of cover.
Accelerated Reader AR
Reading Counts RC
Accelerated Reader
106822
Keywords: Olympics -- Juvenile fiction; Time travel -- Juvenile fiction; Sex role -- Juvenile fiction; Magic -- Juvenile fiction; Tree houses -- Juvenile fiction; JUVENILE FICTION -- Historical -- Ancient Civilizations; JUVENILE FICTION -- Reader -- Chapter Books; JUVENILE FICTION -- Time Travel; Jack (Fictional character : Osborne) -- Fiction; Annie (Fictional character : Osborne) -- Fiction; Olympic games -- Fiction; Greece -- Juvenile fiction; Fantasy fiction -- Juvenile literature; Juvenile works; Fantasy fiction; Fantasy fiction